#1b1t: Investigating Reading Practices at the Turn of the Twenty-first Century - Gruzd, Anatoliy; Rehberg Sedo, DeNel (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2012)
The rise of social networking sites and initiatives such as the One Book, One Twitter book club (#1b1t) make it much easier for readers to share reading experiences on a scale and in a fashion that would not previously have been possible. This paper examines people’s changing reading practices in the age of online social networking. In particular, it aims to describe and explain online conversations around a book called American Gods, the first book of the Twitter book club. Using the automated text analysis and social network discovery software called Netlytic, this study pinpoints a particular time in history that opens new conclusions about the spread of knowledge, education, culture, and ideology. An analysis of the more than 14,000 “tweets” about American Gods provides insight into this world-wide reading group phenomenon, which is now in its second year.